If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3m = -4 Solving 2 + -3m = -4 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3m = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -3m = -4 + -2 -3m = -4 + -2 Combine like terms: -4 + -2 = -6 -3m = -6 Divide each side by '-3'. m = 2 Simplifying m = 2
| 17=(3p-5)+8 | | -6y-2(4y-14)=-22 | | p+18=21 | | f(0)=2(0)+8 | | 17=3+n | | 4(2x+5)=8x+20 | | f(-1)=2(-1)+8 | | v-9=-12 | | 14=4+2t | | x^2+bx-24=0 | | f(-3)=2(-3)+8 | | 7r+5=26 | | 0=v-12 | | f(3)=3-13 | | 5.00l+60.00=11.00l | | 5=9+y(-1) | | 5y^2+125=0 | | f(2)=2-13 | | -9x+10=-9+6x | | f(-1)=-1-13 | | (12x+19)+2(x-10)= | | 36=x+18 | | 30=2x+10 | | f(-2)=-2-13 | | m^2-4m-13=0 | | P-6.7=175 | | 2x^2+11x=-k | | 12f^3-14f^2-40f=0 | | k^2+10k-100=2k^2+55 | | 12+S=20 | | -t-(3)=0 | | y=15x^2-5x-20 |